COMPARATIVE ANALYSIS BETWEEN HOCKEY AND FOOTBALL MALE PLAYERS FOR THEIR SPEED AND AGILITY COMPONENTS - kaur, Romanpreet; Singh, Bakhsis (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The aim of this study was to find out the comparative analysis between hockey and football male players for their speed and agility components. The main purpose of the study was to evaluate the differences between speed and agility of male hockey and football players of Punjabi university, Patiala. The data was collected on 30 male players of hockey and football (H=15 & F=15) of Punjabi university Patiala. For the purpose of data collection Semo Agility test and 50-Meters dash speed test were applied to check their Agility and Speed. After collection of relevant data, paired test was employed on the mean values of measurements of speed and agility. The level of significance was set at 0.05. Findings showed that there was significant difference between hockey and football male players for their agility and speed components.